Shoulder Rotation Affects Trapezius Muscle Activity During Shoulder Horizontal Abduction - Yu, Ilyoung; Kang, Minhyeok (International Journal of Sports Medicine, 2024)
Shoulder horizontal abduction exercise in the prone position is effective for strengthening the lower trapezius muscle. However, this exercise is difficult for patients with acute pain or those undergoing initial rehabilitation because of the postural characteristics of the exercise. This study aimed to (1) investigate the effect of a shoulder horizontal abduction exercise when performed with a different amount of shoulder rotation on the trapezius muscle activation and scapular anterior/posterior tilt angle and (2) evaluate the effect of shoulder rotation on the acromiohumeral distance while sitting. Fifteen healthy men performed shoulder horizontal abduction exercise in three shoulder positions (internal rotation, neutral rotation, and external rotation). During exercises, we measured trapezius muscle activity using an electromyography system and scapular anterior/posterior tilt angle using an inclinometer application. We also measured the acromiohumeral distance using real-time ultrasonography before the exercises. Increases in lower trapezius and middle trapezius muscle activities and a decrease in scapular anterior tilt occurred in shoulder external rotation compared with other positions (p<0.001). Shoulder external rotation also significantly increased acromiohumeral distance in the sitting position (p<0.05). We propose that shoulder external rotation effectively and safely increases middle and lower trapezius muscle activities during the sitting shoulder horizontal abduction exercise.
Keywords: acromiohumeral distance; electromyography; lower trapezius